Impact of Globalization in Central and Eastern Europe and the Role of Higher Education Experience of Babes-Bolyai University, Romania - Arno LOESSNER; Călin HINȚEA (Transylvanian Review of Administrative Sciences, 2005)
Currently there are more than twenty degree programs in public administration at public and private universities in Romania (Hințea, Ringsmuth, 1999). We have selected the public administration program at Babes-Bolyai University (BBU) to examine the impact of globalization, in particular through connection with European and American programs.